2020
DOI: 10.1002/bse.2660
|View full text |Cite
|
Sign up to set email alerts
|

Business model innovation: Identifying foundations and trajectories

Abstract: Business model innovation is an emerging hot topic in management research. It has been developing steadily for 20 years and has gained enormous momentum in recent years. A solid basis has been created, and the first literature reviews summarize the topic. However, an analysis of the core literature and the general foundation of business model innovation literature is missing. This gap is closed with this bibliometric. It analyzes 30 core articles referenced in 380 business model innovation publications. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 67 publications
(204 reference statements)
2
69
0
Order By: Relevance
“…Business model innovation (BMI) is a growing field of discussion in business model (BM) research that mainly focuses on three aspects: value proposition, value creation, and value capture (Dyduch, 2019). BMI is a crucial issue in innovation research where these three elements or their relationships to each other are innovated (Filser et al, 2021). Filser et al (2021) created a holistic framework for BMI based on the existing core in the literature and emerging trends.…”
Section: Vuca Timesmentioning
confidence: 99%
See 2 more Smart Citations
“…Business model innovation (BMI) is a growing field of discussion in business model (BM) research that mainly focuses on three aspects: value proposition, value creation, and value capture (Dyduch, 2019). BMI is a crucial issue in innovation research where these three elements or their relationships to each other are innovated (Filser et al, 2021). Filser et al (2021) created a holistic framework for BMI based on the existing core in the literature and emerging trends.…”
Section: Vuca Timesmentioning
confidence: 99%
“…BMI is a crucial issue in innovation research where these three elements or their relationships to each other are innovated (Filser et al, 2021). Filser et al (2021) created a holistic framework for BMI based on the existing core in the literature and emerging trends. The authors of the study identified four core literature streams: value creation through BMI, strategic BM concepts, design of the BM and its Anna Ujwary-Gil, Anna Florek-Paszkowska, Bianka Godlewska-Dzioboń (Eds.)…”
Section: Vuca Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital technologies should be adapted to distribute movies to consumers. Home distribution and Video-on-Demand are the new industry-standard, which means stakeholders have to change their business models (Bouncken et al 2021;Filser et al 2021; to avoid being eliminated from the value chain. Distributors need to increase their marketing efforts, invest in applications to track the customer experience, and provide such insights to producers to jointly improve their revenues (Franklin et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, due to advances in technology and methodology, the diversity of topics within green aviation industry research has also increased. In the bibliometric field, researchers have long used publication data to investigate the patterns and trends of scientific collaboration (Farrukh et al, 2020; Ferasso et al, 2020; Filser et al, 2020; Kabongo, 2020). However, bibliometric studies in the field of green aviation industry research remain limited.…”
Section: Introductionmentioning
confidence: 99%